The Urgency of the Principle of Justice in Determining Bankruptcy: Challenges of the Emergence of Digital Assets and New Financial Instruments - La Ilman; Muhammad Umar Kalibia; Ide Raunas; Harmoko; Edi Mulyadi (Cita konsultindo, 2026)
The development of digital assets, particularly crypto assets, presents new challenges for the bankruptcy legal system in Indonesia. The technical characteristics of digital assets, which are decentralized, cryptography-based, and difficult to access without private keys, have the potential to disrupt the application of the principles of justice, particularly the principles of Pari passu, transparency, and accountability in determining bankruptcy estates. The problem is further complicated by the transition of crypto asset supervision from BAPPEBTI to the Financial Services Authority (OJK) under the P2SK, which has created a technical regulatory vacuum in the bankruptcy context. This study aims to analyze how the characteristics of digital assets challenge the concept of bankruptcy estates, identify the legal and technical challenges faced by curators, and evaluate the implications of regulatory changes for legal certainty. The study uses a normative juridical method through an analysis of laws and regulations, scientific literature, and a comparison of international practices. The results show that digital assets, normatively, fulfill the elements of assets, but in practice, they pose serious obstacles for curators in the identification, safeguarding, and liquidation processes. Furthermore, the transition of authority to the OJK creates an urgent need for technical regulations to ensure the upholding of the principles of justice in bankruptcy cases involving digital assets. Keywords: Digital Assets, Bankruptcy, Principle of Justice, Bankruptcy Estate, OJK